KOMUNIKASI TERAPEUTIK PERAWAT DENGAN PENDERITA KUSTA DI RUMAH KUSTA BAGANSIAPIAPI ROKAN HILIR - Vinsensia Krismardiana Ayuningtyas; Welly Wirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Therapeutic Communication as one of the scientific study of communication,especially health communication, in the process of treatment and recovery patients, in thiscase involved the nurses with leprosy patient. This study examines the practice of the nurse’stherapeutic communication will influence the patient to get the better mental condition. Theaim of this research is to determine the therapeutic’s phases and attitude of therapeuticcommunication by the nurse’s with leprosy patients at Bagansiapiapi Leprosy Home.The research was conducted at Bagansiapiapi Leprosy Home of Rokan Hilir locatedin Bintang Ujung Street. This study took place from August to October 2016. The methodused in this study is qualitative study. Research subject determined by the method ofpurposive, and data were collected by means observation, interview, and documentation.Results of this research showed that the correct implementation of therapeuticcommunication phases play a role in the recovery of leprosy patient, consisting ofpreparation/pre-interaction phases which the nurse’s prepare before doing nursing,introduction phases to gain the attention and trust patients who conducted approach, phasesof work that allows to change the patient's behavior for the better by providing appropriatetreatment, an the termination phases when treatment and recovery has been completed. Whilethe attitude of therapeutic communication that conducted nurses with leprosy patients amongothers, by the attitude of presenting themselves by taking a position sitting opposite, usingtouch, observe and maintain eye contact, leans toward the patient when speaking, openness,and remain relaxed in response to the patients.